Problems and Solutions of the Hybrid Learning: English Teachers’ Perspective - Kristophorus Lumen Affiantoro; Christina Eli Indriyani (Yayasan Visi Intan Permata, 2025)
Hybrid learning is increasingly being used as an alternative learning method for adult learners. However, hybrid learning still presents several problems for teachers. This study aims to identify the problems encountered by teachers in hybrid learning settings and the solutions that teachers apply to overcome those problems. A case study was employed using a qualitative method by interviewing two teachers who experience teaching business communication class in one of the media companies in Jakarta. The business communication class is conducted in hybrid mode, in which students synchronously join the class both offline and online. The results show that teachers encountered problems comprising six aspects: planning, engagement, interaction/communication, technology, assessment, and language skill teaching. Both teachers can provide solutions, but problems related to student disengagement still could not be resolved. In response to the problems, the teachers are expected to implement collaborative learning and build emotional resilience. Furthermore, it is recommended for the companies to provide adequate training for teachers and structured planning to support the specific demands of hybrid learning teaching.